The Obstacle Factors in Speaking Performance by the 4th Semester Students of the English Department at UKI Toraja - Dan Mangoki' (Teaching English as a Foreign Language Overseas Journal, 2020)
This research aims to find out the Obstacles Factor in Speaking Performance by the Fourth Semester Students of the English Department at UKI Toraja. The method of this research is qualitative descriptive method. The population of this research is the Fourth Semester Students of the English Department at UKI Toraja. The data were collected through interview by using analysis from Miles and Huberman theory. The results of the data shows that the Fourth Semester students of the English Department at UKI Toraja have some obstacles factor in speaking performance. This evident based on the factor of obstacles in speaking performance can be divided to internal factor and external factor. The obstacles factor that are often appear are: (1) Lack of motivation (2) Lack of vocabulary needed to talk (3) Poor in grammar (4) Poor in pronunciation (5) Unwillingness (6) Shyness (7) Lack of Self-confidence (8) Anxiety (9) Fear of language evaluation (10) Performance condition (11) Lack of practice (12) Low of classroom interaction and (13) The teacher method used in teaching not effective.